Effects of Grain Size Distribution on Landslide Dam Breaching—Insights From Recent Cases in China - Mei, Shengyao; Chen, Shengshui; Zhong, Qiming; Shan, Yibo (Frontiers in Earth Science, 2021)
Landslide dams are common geological features in mountainous areas, which may have serious consequences due to sudden breaching of the dam. An effective emergency response requires rapid and accurate forecasts regarding the landslide dam breach process. However, most existing models use physical, mechanical, and erosion properties of the mean or characteristic grain sizes to represent the landslide deposits. The grain size distribution and variations in soil erodibility with the depth in the landslide dam are not considered, resulting in an incorrect estimation of the breach flow hydrograph. In this paper, a simplified landslide dam classification is presented based on the formation mechanism and grain size distribution of landslide dams. Additionally, the influences of grain size distribution on the residual dam height and breach process of landslide dams are analyzed. This paper proposes a numerical method to rapidly obtain the breach hydrographs and breach morphology evolution of landslide dams. The new method can quickly classify landslide dams according to geological survey data and predict the landslide dam breach process. Three types of representative landslide dams in China are simulated to validate the proposed method. The breach flow discharge is significantly affected by spillway excavation. This contribution can provide rapid prediction of the landslide dam breach process and can be used for the emergency response planning before dam breaching.